Molecular genetic analysis of Lafora Disease and Dravet's Syndrome - Salar, Seda. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Lafora Disease (LD), a type of Progressive Myoclonus Epilepsy (PME) and Dravet’s Syndrome (DS), the most severe form in Generalized Epilepsy with Febrile Seizure Plus (GEFS+) spectrum, are debilitating examples of epilepsy syndromes. Early diagnosis is critical for distinguishing these diseases from other epilepsy syndromes and for developing effective treatment strategies as patients with these diseases are generally resistant to drug treatment. Molecular genetic analysis of genes that are involved in the development of such severe forms of epilepsy is essential for early diagnosis. LD is associated with two genes, EPM2A and EPM2B encoding laforin, a dual specificity phosphatase and malin, an E3 ubiquitin ligase proteins, respectively. DS is frequently associated with SCN1A gene encoding α subunit of voltage-gated sodium channel type 1 (Nav1.1). All molecular genetic analysis in the relevant genes were carried out by PCR amplifications of all coding regions followed by DNA sequence analysis. Mutational analysis of EPM2A and EPM2B genes on 4 patients suspected to have LD revealed a novel nonsense mutation in the EPM2B gene of two sisters and a recurrent nonsense mutation in the EPM2A gene in the third patient, confirming the clinical diagnosis. The fourth patient who did not have any changes in both EPM2A and EPM2B genes was analyzed for point mutations in the EPM1A gene by direct sequencing since LD and Unverricht-Lundborg disease (ULD) caused by mutations in the EPM1A gene can not be easily distinguished clinically. ULD diagnosis was also excluded in this patient. Mutational analysis of SCN1A gene on 4 patients, one suspected to have GEFS+ and 3 suspected to have DS revealed two novel mutations, a missense mutation and a dinucleotide deletion in two patients. The non-polymorphic nature and evolutinary conservation of the missense mutation indicated that the mutation may have a major effect on the phenotype and hence cause DS. The third patient suspected to have DS and the patient suspected to have GEFS+ did not have any changes in the SCN1A gene. The DNA analysis results along with the information about the good prognosis of two DS patients suggested that they may also be considered in the GEFS+ spectrum. The GEFS+ patient on the other hand can be screened for other genes relevant to GEFS+ phenotype. In conclusion, mutational analysis of EMP1A, EPM2A, EPM2B and SCN1A genes were successfully implemented through direct DNA sequencing of the coding regions as an initial study to aid the clinical diagnosis and further to reveal the prevalence and molecular pathology of LD and DS in Turkey.
Keywords: Myoclonus -- Genetic aspects.; Epilepsy -- Genetic aspects.